Revision of Afrotropical Suragina Walker, 1859 (Diptera, Athericidae) - Burgert S. Muller; Vaughn R. Swart; Louwrens P. Snyman (African Invertebrates)
Suragina Walker, 1859 of the Afrotropical Region are revised. Nineteen species are recognised and treated within. The species Suragina bilobata Muller, sp. nov., S. copelandi Muller, sp. nov., S. freidbergi Muller, sp. nov., S. liberiaensis Muller, sp. nov., S. malavaensis Muller, sp. nov., S. mulanjeensis Muller, sp. nov., S. semiobscura Muller, sp. nov. and S. zombaensis Muller, sp. nov. are described as new. A key to the known males and females of 17 Afrotropical species, excluding S. disciclara (Speiser, 1914) and S. pilitarsis (Lindner, 1925), is provided. Additionally, S. bivittata (Bezzi, 1926) is designated as junior synonym of S. binominata (Bequaert, 1921). Similarly, S. varicolor (Brunetti, 1929) is designated as junior synonym of Suragina bezzii (Curran, 1928). The distribution of Afrotropical Suragina is expanded with six new distribution records of three species: S. agramma (Bezzi, 1926): Kenya and Malawi; S. bezzii: Burundi, Kenya, and Uganda; S. binominata: Malawi.